In vivo quantitation of regional cerebral blood flow in glioma and cerebral infarction: validation of the HIPDm-SPECT method. - Drayer, B; Jaszczak, R; Friedman, A; Albright, R; Kung, H; Greer, K; Lischko, M; Petry, N; Coleman, E (American Journal of Neuroradiology, 1983)
Iodine-123 labeled hydroxyiodopropyldiamine (HIPDm) is a diffusible indicator with an 85%-90% extraction fraction and stable retention in the brain for more than 2 hr. Equilibrium-phase imaging and quantitation using single-photon emission computed tomographic (SPECT) scanning defined a distribution of HIPDm in proportion to regional cerebral blood flow (rCBF). Studies in calves affirmed a close correspondence (r = 0.97) in calculated rCBF between HIPDm and microspheres using the tissue deposition-arterial input function microsphere methodology. Using this same mathematical analysis in vivo, reproducible rCBF data within the expected range of normal were obtained on repeated studies in the same nonhuman primate. With a diffuse encephalopathy secondary to subarachnoid blood, a bilaterally symmetric decrease in rCBF was present. A prominent focal decrease in HIPDm accumulation and calculated rCBF was noted with cerebral infarction in the distribution of a ligated middle cerebral artery. Patient studies with glioma revealed diminished HIPDm accumulation due to decreased flow and/or pH in the region of the neoplasm as well as in the associated vasogenic edema and overlying gray matter.